2020
DOI: 10.1166/jnn.2020.18580
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Quercetin Nanocrystals with Different Particle Sizes

Abstract: As one of the most prospective delivery systems of insoluble drugs, nanocrystal has attracted more and more attention from pharmaceutical researchers. Nanoparticles with prominent different particle diameters were obtained to solve the problem of solubility and evaluate the positive effects of quercetin in vitro. The newly prepared nanocrystals were investigated by several methods including dynamic light scattering (DLS) and transmission electron microscopy (TEM). The particle sizes of the quercetin nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We observed a significant GPx and SOD depletion that might be a mechanism for the Escherichia coli infection in rabbits, quercetin is able to increased GPX and SOD levels and this effect may also participate in protection against Escherichia coli infection, but for the first time here, we showed that antioxidant potential of quercetin nanoparticles was significantly increased in GPx than quercetin in both normal and infected rabbits. So, nano-sized quercetin particles more effective than quercetin and lead to the efficiency of antioxidant defence systems activity and this in agreement with Zhang et al (2020) who confirmed that nanoparticles with prominent different particle diameters were solved the problem of solubility and evaluate the positive effects of quercetin in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…We observed a significant GPx and SOD depletion that might be a mechanism for the Escherichia coli infection in rabbits, quercetin is able to increased GPX and SOD levels and this effect may also participate in protection against Escherichia coli infection, but for the first time here, we showed that antioxidant potential of quercetin nanoparticles was significantly increased in GPx than quercetin in both normal and infected rabbits. So, nano-sized quercetin particles more effective than quercetin and lead to the efficiency of antioxidant defence systems activity and this in agreement with Zhang et al (2020) who confirmed that nanoparticles with prominent different particle diameters were solved the problem of solubility and evaluate the positive effects of quercetin in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…Efforts have been made to overcome these challenges, by incorporating QR into various carriers, such as polymeric conjugates ( 14 ), micelles ( 15 ), emulsions ( 16 ), liposomes ( 17 ) and nanocrystals ( 18 ). The modification of QR nanoparticles with silver nanoparticles showed a significant improvement in antibacterial effect against drug-resistant Escherichia coli and Staphylococcus aureus ( 19 ).…”
Section: Introductionmentioning
confidence: 99%